Analisis Struktur Baja dengan Perhitungan Beban Gempa Menggunakan Metode Time History Berdasarkan SNI 1726:2012 dan SNI 1729:2015 - G. Turu’allo; A.H. Anggara (Civil Engineering Department, Tadulako University, 2023)
The selection of material types used in designing a building is one of essential parts since every type of material consisted of different elements. One of primary materials in constructing building structure is steel. The use of steel has been implemented in most building structures nowadays for its high performance of ductility compared to concrete and wood. Ductility is an important requirement to achieve building structure that is resistant to earthquake. In this thesis, there will be an elaboration of an earthquake resistant and steel structured building. The designed building will be a five-floor office configured by an organized structure. The steel framework system of specialized moment loader is used as structure system of earthquake resistance and analysed using time history method. The steel material used has A36 grade (fy = 250 MPa; fu = 400 MPa), and the concrete grade f’c = 30 MPa. The preparation process results in a design of an earthquake steel resistant structure building that meets the requirement of intersection between each floor and the maximum intersection value occurs on second floor with 93,5 mm where the legal supposed intersection has been valued on 95 mm. The dimension of structure element used is profile block W 14 x 6,75 x 38 for the x-axis and W 16 x 7 x 40 for y-axis. It also has 12 cm of plate thickness on every level with profile column of Wx14x16x283